2020
DOI: 10.1080/14737159.2020.1724092
|View full text |Cite
|
Sign up to set email alerts
|

A look into the use of Raman spectroscopy for brain and breast cancer diagnostics: linear and non-linear optics in cancer research as a gateway to tumor cell identity

Abstract: Introduction: Currently, intensely developing of linear and non-linear optical methods for cancer detection provides a valuable tool to improve sensitivity and specificity. One of the main reasons for insufficient progress in cancer diagnostics is related to the fact that most cancer types are not only heterogeneous in their genetic composition but also reside in varying microenvironments and interact with different cell types. Until now, no technology has been fully proven for effective detecting of invasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 100 publications
(146 reference statements)
0
28
0
Order By: Relevance
“…However, the transfer of the “Raman spectral library”, such as those available in FTIR analyses, remains a major challenge that stands in the way of clinical translation for Raman-based technologies, and continued effort is needed to facilitate the transition from benchtop to bedside by developing novel experimental designs and structured protocols for the objective method. The further development of the cell classification methods, the improvement in Raman instrumentations trending toward obtaining data with greater resolution, shorter collection times, and higher accuracy would give additional information, allowing earlier and more accurate diagnosis, reducing the need for human intervention, and increasing the objectivity of assessment [ 11 , 63 ].…”
Section: Summary and Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…However, the transfer of the “Raman spectral library”, such as those available in FTIR analyses, remains a major challenge that stands in the way of clinical translation for Raman-based technologies, and continued effort is needed to facilitate the transition from benchtop to bedside by developing novel experimental designs and structured protocols for the objective method. The further development of the cell classification methods, the improvement in Raman instrumentations trending toward obtaining data with greater resolution, shorter collection times, and higher accuracy would give additional information, allowing earlier and more accurate diagnosis, reducing the need for human intervention, and increasing the objectivity of assessment [ 11 , 63 ].…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…On a different note, Raman imaging can overcome problems resulting from limited stability, bleaching, the use of external biomarkers and long sample preparation associated with traditional morphological analysis like electron microscopy and fluorescence microscopy, opening the way to in vivo analysis. Raman microscopy (RM) can be a complement to conventional staining methods that can be easily used for monitoring the sub-cellular components of normal and cancer cells [ 10 , 11 ]. Therefore, the application of RM can be used as a non-invasive method for the early diagnosis of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy offers the ability to probe biochemical changes in mitochondria, lipid droplets, nuclei, cytoplasm, membrane and visualize the complex molecular events directly in living normal and cancer cells in vitro, ex vivo human tissues and in vivo animal models. 3,4 It is also demonstrated as a versatile clinical diagnostic tool with numerous successful reports on the detection of cancerous tissues in human patients. [5][6][7][8] Our goal was to demonstrate possibility of monitoring of redox state changes occurring in mitochondrial b-and c-type cytochromes in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming clear that changes in metabolism during cancer development are governed by balance between the need of the cell for energy supply with its equally important need for macromolecular building blocks and maintenance of redox balance. Regarding macromolecular building blocks the role of fatty acids as critical bio-energetic substrates within the glioma cells [6][7][8][9][10][11][12][13] and breast cells 10 has been recognized.…”
Section: Introductionmentioning
confidence: 99%
“…Existing clinical technologies-including state-of-the-art surgical microscopy, fluorescence-guided surgery and magnetic resonance imaging (MRI, used either pre-or intra-operatively)-cannot detect the full extent of cancer invasion. 7 The imaging methods that use radio-labelled ligands are not effective for detecting malignant gliomas. It has been reported that thirty five to forty percent of recurrent gliomas in human patients are not observed using positron emission tomography imaging techniques based on fluorodeoxyglucose uptake (e.g., FDG-PET), despite being detected by contrast MRI.…”
mentioning
confidence: 99%